Utilization of Borane-Catalyzed Hydrosilylation as a Dearomatizing Tool: Six-Membered Cyclic Amidine Synthesis from Isoquinolines and Pyridines - Cao, Vinh Do; Jo, Dong Geun; Kim, Huiae; Kim, Changeun; Yun, Seula; Joung, Seewon (Synthesis, 2020)
In this study, a convenient strategy to synthesize six-membered cyclic amidines from isoquinolines and pyridines has been developed. Borane-catalyzed hydrosilylation of each N-heteroarene was utilized as a dearomatizing tool. Substrate scope is broad with respect to both isoquinolines and pyridines, with various reaction pathways depending on the substitution pattern of the N-heteroarenes. The reaction mechanism and reactivity of each class of N-heteroarenes has been discussed. The resulting six-membered (Z)-sulfonyl amidine products are rarely reported and are mostly unprecedented. The scalability of this method and versatility of the cyclic amidine products are also presented.
Keywords: cyclic amidine; hydrosilylation; N-heteroarenes; dearomatization; [3+2] cycloaddition; B(C6F5)3